(untitled) (Acta Scientiarum. Animal Sciences, 2020)
The aim was to evaluate the proximate food composition, cholesterol content, coloring and economic aspects of the main nutrients present in by-products from the slaughter of cattle. The samples were collected from 14 organs, with four repetitions each, of which we conducted the analyses of moisture, crude protein, mineral matter, cholesterol and fat content. The color was measured through the coordinates L*, a*, b*. The differences between the groups of red and white viscera were evaluated by contrasts analysis. Subsequently, the data were subjected to multivariate analysis of variance, which was complemented by the principal component technique. In the analysis of contrast between red and white viscera, the results showed that the components with the highest content of total fat does not necessarily have the highest content of cholesterol and vice-versa. For minerals, the red viscera presented higher content than white viscera and, in order to analyze the protein composition, there was less variability for red viscera in relation to white viscera. In the color analysis, the values for the color readings indicated uniformity between the external and internal readings, except for the tongue. On mean, the proximate composition values for the offals are similar to the values for beef, especially regarding the red viscera.